Pengaruh Kepuasan Kerja dan Keterikatan Kerja Terhadap Kinerja Karyawan - Syarif Khalid Attamimi; Keumala Hayati; Mirwan Karim (Penerbit Goodwood, 2022)
Purpose: This study seeks to determine the influence of job satisfaction and work engagement on PT Golden Sari Lampung employees' performance. In principle, every company always expects its employees to work optimally to increase profits and help accelerate the achievement of other organizational goals. Someone with a high work engagement will tend to show the best performance because they enjoy their work. Employees who have an attachment to their work will certainly show enthusiasm and dedication and fully concentrate on work so that employees can show their best performance in doing their job. Research methodology: This study's data collection method used a Likert scale questionnaire. The sample used in this study was 150 respondents. The data analysis tool used is multiple linear regression analysis, t-test, and f-test. Results: This study's results indicate that job satisfaction positively affects performance, and work engagement positively affects performance. Limitations: The factors that affect employee performance used in this study are only the variables of job satisfaction and work engagement. At the same time, many other variables can be factors that affect the performance of employees of a company. Contribution: The company should be open to every aspiration conveyed by employees and provide opportunities for them to express opinions in decision-making. It is done so that employees feel more influence over what happens to the company. In addition, the management of PT Golden Sari Lampung should foster a sense of kinship and emotion toward the company so that employees feel comfortable and full of concentration in every job.